Feasibility of a reablement-program in a Swedish municipality. (2nd January 2023) - Zingmark, Magnus; Kylén, Maya
Abstract: Background: While occupational therapists (OT) and physiotherapists (PT) have a central role in reablement, no structured approach for these professions has been described in Sweden. Aims/Objectives: The aim was to explore the feasibility of a reablement program developed to guide OTs and PTs in a Swedish municipality context. Material and methods: Eligible participants were OTs and PTs working with reablement. Feasibility was evaluated in terms of how OTs ( n = 16) and PTs ( n = 15) experienced the application of the program. Data were collected through web surveys during a pilot study over four months. Results: The program was implemented for 62 clients. Baseline assessments were conducted in 97% of all cases and follow-ups in 77%. The average duration of the program was 8 weeks and includeed 5 home visits and 3 contacts by phone. In 15 cases, a new goal was identified after follow-up. Collaboration was included with other professionals and relatives in 89% and 35% of the cases, respectively. The program was categorized as feasible to some extent in 34 cases and not feasible in 21 cases. Conclusions and significance: The program was feasible to some extent. To enhance feasibility, flexibility may be needed in order to tailor assessments according to the client's health status.